HUBUNGAN ANTARA REGULASI DIRI DENGAN MOTIVASI MENYELESAIKAN SKRIPSI - Ajeng Pratiwi; Hadi Pranoto; Achmad Irfan Muzni (Universitas Muhammadiyah Metro, 2026)
Self-regulation and motivation to complete An Undergraduate thesis have an important role in final year students in working on the thesis. However, the low motivation to complete the thesis in students becomes an obstacle in the process of preparing the thesis, such as easily despairing if they do not find reading sources, lazy to revise after guidance, as a result students are delayed to graduate on time. The purpose of this study was to determine whether or not there was a relationship between self-regulation and motivation to complete the thesis on Guidance and Counseling students at Muhammadiyah University of Metro.This study used a quantitative research design with a type of correlation or relationship. The population in this study were Guidance and Counseling students who had received an advisory decree. The sample in this study used a saturated sample with a sample size of 25 Guidance and Counseling students who had received an advisory decree. The research results obtained were the correlation coefficient (r) between the self-regulation variable and the motivation to complete the thesis of 0.469. Then it was known that the result (r square) was 0.220, this means that the contribution of self-regulation to the motivation to complete the thesis was 22% and 78% was influenced by other variables. The conclusion of this study was that there was a significant relationship between self-regulation and motivation to complete the thesis.